Effect of ethylene glycol on polymeric membrane fabrication for membrane distillation - Chong, K. C. (Trans Tech Publications Ltd, 2016)
Membrane distillation (MD) is a membrane separation process first introduced in 1963 by Bodell whereby the major driving force is by vapor pressure difference between the feed and permeate induced by temperature gradient. The MD applications mainly focus on seawater desalination and other industry application such as extraction of fruit juice. In this study, hydrophobic polyvinylidene fluoride (PVDF) hollow fiber membranes were fabricated by wet/dry phase inversion method with 1-methyl-2-pyrrolidone (NMP) as solvents and ethylene glycol (EG) as non solvent additives. The effect of the additives on the membrane formation was studied based on the results from membrane morphology investigation through scanning electron microscope (SEM) and porosity calculation based on gravitational method. The SEM image indicated the membrane morphology changed from finger like layer extending from inner to outer surface to a finger like layer separated by microvoid attributed addition of ethylene glycol which might lead to permeate flux enhancement. Furthers, results from the gravitational test reveal that the addition of ethylene glycol demonstrated a positive effect on the porosity of the membrane. Later, the membranes were tested by membrane distillation process in sodium chloride removal varying feed inlet temperature to investigate the permeate flux performance of the membrane.